Study of the Education Community's Interest in Digital Competition-based Products - Fajar Julian Santosa; Lutfi Andriani; Drajat Tri Kartono; Herlinda Nur Fitriana; Velda Fiska Saputri (Ittishal Educational Research Journal, 2025)
The era of Industrial Revolution 4.0 has had a significant impact on the development of education, one of which is through the transformation of digital technology. This research aims to deepen understanding the education community's interest in digital competition-based products. This research is development research using the ADDIE Research and Development (R&D) method to develop online-based training and competition products. The data collection stage was carried out through a survey of 185 respondents. The data was then analyzed using the descriptive statistics method. The research results show that public interest in digital competition-based products is significant. Interest in digital competition-based products was demonstrated by 80% or 148 people interested in digital competition-based products. It was found that many respondents showed high interest in using digital competition-based products as interactive, flexible, and exciting learning tools.